2022
DOI: 10.1007/s00604-022-05167-y
|View full text |Cite
|
Sign up to set email alerts
|

A review on corona virus disease 2019 (COVID-19): current progress, clinical features and bioanalytical diagnostic methods

Abstract: A new epidemic of acute respiratory viral pneumonia was discovered in central China at the end of 2019. The disease was given the name coronavirus disease 2019 (COVID-19), and the virus that caused this disease was known as severe acute respiratory syndrome coronavirus (SARS-CoV-2). So far, diagnostic methods have been focused on (a) human antibody detection, (b) viral antigen detection and (c) viral gene detection, the latter using RT-PCR being the most accurate approach. In this paper, we present a summary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 125 publications
(151 reference statements)
0
18
0
Order By: Relevance
“…However, COVID-19 still spreads in many countries around the world, posing a serious threat to people's lives and health and a huge burden on the global economy and health [18,19]. COVID-19 may cause pulmonary fibrosis, which may affect the prognosis of patients [20]. Previous studies by many scholars have demonstrated that lung fibers, as sequelae, seriously affect lung function and the quality of life of patients [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, COVID-19 still spreads in many countries around the world, posing a serious threat to people's lives and health and a huge burden on the global economy and health [18,19]. COVID-19 may cause pulmonary fibrosis, which may affect the prognosis of patients [20]. Previous studies by many scholars have demonstrated that lung fibers, as sequelae, seriously affect lung function and the quality of life of patients [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent review articles (2021–2022) refer to optical immunosensors, often among other topics of interest in the field of biosensing. Thus, some of these articles describe optical immunosensors that have been developed for various (groups of) biomolecules [ 1 , 41 , 42 ], such as COVID-19-related biomarkers [ 43 , 44 , 45 , 46 ]. Immunosensing based on optical fiber technology [ 47 , 48 ] and application of spectroscopic ellipsometry to immunosensing [ 49 ] have been presented in recent reviews.…”
Section: Newest Developments In Optical Immunosensors: Bioanalytical ...mentioning
confidence: 99%
“…Thus, several of the relevant articles present new optical immunosensors for the detection/quantification of proteins of the SARS-CoV-2 virus or human antibodies developed against them [ 65 , 66 , 71 , 84 ]. Moreover, due to the COVID-19 pandemic outbreak and the consequent high interest in new tools for COVID-19 diagnosis, several recent review articles have presented, among other analytical approaches, research efforts toward development of optical immunosensors associated with COVID-19 [ 43 , 44 , 45 , 46 , 83 ]. Several optical immunosensors have been developed for the detection of whole bacteria, such as Staphylococcus aureus [ 68 ], especially methicillin-resistant Staphylococcus aureus [ 54 ], Salmonella typhi VI [ 59 ], Escherichia coli O157 [ 60 ], and Salmonella typhimurium [ 88 ].…”
Section: Newest Developments In Optical Immunosensors: Bioanalytical ...mentioning
confidence: 99%
“…We try to give a comprehensive view of the role of these nanoparticles in the designing of biosensors. Unlike the recently published review articles [ 23 29 ] that covered the performed studies on the SARS-CoV-2 diagnosis in 2020–2021, this manuscript focuses on the newest trends for the sensing of all human coronaviruses using the AuNPs from the beginning of the COVID-19 epidemic until 2022. This paper includes a detailed overview of biosensing strategies using the varied transducers (electrochemical, optical, etc.)…”
Section: Introductionmentioning
confidence: 99%